2022
DOI: 10.1002/adfm.202205918
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a 2D Hybrid Silver/Antimony‐Based Iodide Double Perovskite Photoferroelectric with Photostrictive Effect and Efficient X‐Ray Response

Abstract: 2D hybrid halide double perovskites (HHDPs) have been demonstrated to be a promising alternative to conventional lead-based halide perovskites as a new system of photoferroelectrics, due to their unique characteristics of environmental friendliness, favorable stability, and fascinating optoelectronic properties. Herein, for the first time, a 2D iodide double perovskite photoferroelectric is reported based on Ag/Sb ions, (4,4-DFPD) 4 AgSbI 8 (4,4-DFPD = 4,4-difluoropiperidinium), which possesses a high Curie te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…Under high bias voltage of −80 V, the detector shows an impressive value of 8120 μC Gy air −1 cm −2 and even for the low bias voltage, it also delivers a 3859 μC Gy air −1 cm −2 sensitivity value, much higher than those of the lead-free perovskites, such as MA 3 Bi 2 I 9 (1947 μC Gy air −1 cm −2 ), (BA) 2 CsAgBiBr 7 (4.2 μC Gy air −1 cm −2 ), (chloropropylammonium) 4 AgBiBr 8 (0.8 μC Gy air −1 cm −2 ), and (4,4-difluoropiperidinium) 4 AgSbI 8 (704.8 μC Gy air −1 cm −2 ). 23–25…”
Section: Resultsmentioning
confidence: 99%
“…Under high bias voltage of −80 V, the detector shows an impressive value of 8120 μC Gy air −1 cm −2 and even for the low bias voltage, it also delivers a 3859 μC Gy air −1 cm −2 sensitivity value, much higher than those of the lead-free perovskites, such as MA 3 Bi 2 I 9 (1947 μC Gy air −1 cm −2 ), (BA) 2 CsAgBiBr 7 (4.2 μC Gy air −1 cm −2 ), (chloropropylammonium) 4 AgBiBr 8 (0.8 μC Gy air −1 cm −2 ), and (4,4-difluoropiperidinium) 4 AgSbI 8 (704.8 μC Gy air −1 cm −2 ). 23–25…”
Section: Resultsmentioning
confidence: 99%
“…Neighboring molecules in the stack rely on weak hydrogen bonding C–H/O/N and van der Waals forces. As shown in Figure , Hirshfeld surface calculation shows that H-All accounts for 81.7%, O-All accounts for 18.1%, and N-All accounts for only 0.2%, revealing that the intermolecular forces of 1-R and 1-S are mainly concentrated between H atoms and O atoms. As shown in Figure S6, both 1-S and 1-R molecules have large dipole moments of 6.1351 Debye.…”
Section: Resultsmentioning
confidence: 94%
“…BX 6 octahedra in the reported ferroelectric OIHPs also have considerable diversity, with a variety of optional B-site metal ions such as Pb 2+ , Mn 2+ , Cd 2+ , Cr 2+ , Sn 2+ and so on. 51–58 Notably, Xiong et al reported a special nickel( ii ) nitrite-based organic–inorganic hybrid perovskite ferroelectric, [ N -fluoromethyl tropine][Ni(NO 2 ) 3 ], designed by rational chemical modification and structural assembly. 59 Zhang et al also reported several zero-dimensional packing phase transition materials with the Ni(NCS) 6 framework.…”
Section: Introductionmentioning
confidence: 99%